The Askîy Project—Empowering Youth, Inspiring Research. (April 2020) - Martin, Wanda; Hanson, Yvonne
Urban agriculture is one way to connect people with the food system and can empower urban youth who may feel disconnected from the land. The award winning askîy project is a multifaceted program supporting both Indigenous and non-Indigenous youth in a core neighborhood in Saskatoon, Saskatchewan Canada.